HUBUNGAN PENGETAHUAN MASYARAKAT TENTANG HIV/AIDS DENGAN TERJADINYA DISKRIMINASI PADA ODHA - Salami Salami; Fia Dewi Auliani (Jurnal Sains Riset, 2021)
Human Immunodeficiency Virus (HIV) is a virus that attack the immune system that causes the body susceptible to disease. HIV is the cause of Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms of the disease that attacks the body due to immune system down. One of the obstacles preventing and preventing HIV / AIDS in Indonesia is the high discrimination in people with HIV/AIDS (PLWHA). The purpose of this study to determine the relationship of knowledge about HIV/AIDS community with the occurrence of discrimination in people living with HIV.This research use cross sectional approach. The sample of this study is the Gampong Mulia community as many as 97 respondents. The results showed that most of the respondents had good knowledge about HIV/AIDS as well as low discrimination of 40 respondents (41,2%), respondents with high discrimination and poor knowledge (24,7%). Based on chi square test showed that there is correlation of knowledge about HIV/AIDS with discrimination on PLWHA (p – value = 0,005, p – value 0,05)Keywords: HIV/AIDS, Discrimination, PLWHA